Microstructure and surface morphology of YIG and 2 wt% Ce-doped YIG thin films synthesized via sol-gel method - Singh B.K.; Mishra S.K. (My University, 2025)
The Y3Fe5O12bulk material has been extensively investigated owing to its unique spin dynamic and magneto-optical properties such as low damping and infrared absorption that desired in various device applications. To meet the demand of a cost-effective growth method, in this work we report the synthesis of pristine and doped yttrium iron garnet films through the conventional sol-gel method. The Y3Fe5O12and CexY3-xFe5O12(x = 0.02) films were grown on amorphous Si (1 0 0) substrates. The structural and morphological properties of Y3Fe5O12and CexY3-xFe5O12(x = 0.02) thin films were investigated with x-ray diffraction. Experimental results suggest that the films were grown in pure garnet polycrystalline phase. The morphology of the films explored by atomic force microscopy (AFM). Obtained micrographs indicate the presence of small pores and grains on the top surface. The microstructural study of the film surface by scanning electron microscopy (SEM) and AFM suggest that the average roughness's of thin films varies in the range of 1.2 and 6.3 nm, respectively for Y3Fe5O12and CexY3-xFe5O12(x = 0.02) thin films. These findings suggest the successful growth of garnet thin films that exhibits excellent structural and morphological properties. © 2021 Elsevier Ltd. All rights reserved.